GALE Phase 4 Chinese Broadcast Conversation Parallel Sentences - Song, Zhiyi; Krug, Gary; Strassel, Stephanie (Linguistic Data Consortium, 2015)
GALE Phase 4 Chinese Broadcast Conversation Parallel Sentences was developed by the Linguistic Data Consortium (LDC). Along with other corpora, the parallel text in this release comprised training data for Phase 4 of the DARPA GALE (Global Autonomous Language Exploitation) Program. This corpus contains Chinese source sentences and corresponding English translations selected from broadcast conversation data collected by LDC in 2008 and transcribed and translated by LDC or under its direction.